2018
DOI: 10.25165/j.ijabe.20181106.4061
|View full text |Cite
|
Sign up to set email alerts
|

Determining soil organic carbon concentration in agricultural fields using a handheld spectroradiometer: Implication for soil fertility measurement

Abstract: The soil organic carbon (SOC) plays a vital role in plant growth and development, and therefore is considered as one of the most important indicators of soil quality. This study was carried out in the central region of Saudi Arabia to explore the potential of spectroscopy in determining the SOC concentration in low-fertility soils. Spectral reflectance data were collected, under the controlled laboratory conditions on 39 air-dried 2.0 mm sieved soil samples, using a handheld spectroradiometer of a wavelength r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, soils collected at 30 cm showed higher reflectance, higher gypsum and less SOC ( Table 1). Lower SOC content lead to higher reflectance, which is frequent in drylands [35,62], especially when calcium carbonate and gypsum are abundant in soils [27]. Differences in soil reflectance of the plot of study can be observed by brightness index calculated from Sentinel 2 images ( Figure 1d).…”
Section: Prediction Of Physical-chemical Propertiesmentioning
confidence: 96%
“…However, soils collected at 30 cm showed higher reflectance, higher gypsum and less SOC ( Table 1). Lower SOC content lead to higher reflectance, which is frequent in drylands [35,62], especially when calcium carbonate and gypsum are abundant in soils [27]. Differences in soil reflectance of the plot of study can be observed by brightness index calculated from Sentinel 2 images ( Figure 1d).…”
Section: Prediction Of Physical-chemical Propertiesmentioning
confidence: 96%
“…The Walkley-Black (colorimetric) method using a spectrophotometer and following FAO (2019) and Tola et al (2018) procedures was used. Soil organic carbon content was calculated according to the Equation 1 (Haile et al, 2021); SOC= %.OC ˟ 𝜌ƅ ˟ d………………... (Equation 1) Where; % OC is the soil organic carbon concentration, 𝜌ƅ is soil bulk density (gcm -3 ), and d is the soil depth of the sample (cm).…”
Section: The Description Of the Area Of The Studymentioning
confidence: 99%
“…At larger scale, Schillaci et al (2016) and Darwish and Fadel (2017) prepared SOC maps for the Mediterranean region/Arab region. At the regional scale, Tola et al (2018Tola et al ( , 2019 assessed the SOC concentration in the parts of Al-Kharj region of Saudi Arabia, with special emphasis on the long-term impact of tillage on the soil organic carbon. Another study by Mallick et al (2020) was developed SOC prediction models for Asir Province, Saudi Arabia.…”
mentioning
confidence: 99%